The Method of teaching Biology in School using Modular Technology (Journal of Educational Sciences, 2018)
On this article, we present the methods of teaching modular technologies in school. The use ofmodular technology at the lessons of biology provides development of the motivational sphere of the student, his intellect, abilities, independence, ability to exercise self-management in educational and cognitive activities. I was convinced that lessons based on this technology stimulate students to independentlythink, develop their skills to navigate in a new situation, find their ways to solve problems, master various ways of obtaining knowledge, encourage independence of judgments, and ensure highquality of knowledge.Key words: modular technology, innovation, methodology, didactics, psychophysiology.